Arsenic‐containing hydrocarbons and arsenic‐containing fatty acids: Transfer across and presystemic metabolism in the Caco‐2 intestinal barrier model. Issue 10 (3rd August 2015) - Meyer, Sören; Raber, Georg; Ebert, Franziska; Taleshi, Mojtaba S; Francesconi, Kevin A; Schwerdtle, Tanja
<x xml:space="preserve">Abstract</x> Scope Arsenic‐containing hydrocarbons (AsHCs) and arsenic‐containing fatty acids (AsFAs) represent two classes of arsenolipids occurring naturally in marine food. Toxicological data are yet scarce and an assessment regarding the risk to human health has not been possible. Here, we investigated the transfer and presystemic metabolism of five arsenolipids in an intestinal barrier model. Methods and results Three AsHCs and two AsFAs were applied to the Caco‐2 intestinal barrier model. Thereby, the short‐chain AsHCs reached up to 50% permeability. Transport is likely to occur via passive diffusion. The AsFAs showed lower intestinal bioavailability, but respective permeabilities were still two to five times higher as compared to arsenobetaine or arsenosugars. Interestingly, AsFAs were effectively biotransformed while passing the in vitro intestinal barrier, whereas AsHCs were transported to the blood‐facing compartment essentially unchanged. Conclusion AsFAs can be presystemically metabolised and the amount of transferred arsenic is lower than that for AsHCs. In contrast, AsHCs are likely to be highly intestinally bioavailable to humans. Since AsHCs exert strong toxicity in vitro and in vivo, toxicity studies with experimental animals as well as a human exposure assessment are needed to assess the risk to human health related to the presence of AsHCs in seafood.